Pemanfaatan Bank Sampah sebagai upaya Peningkatan Pendapatan Masyarakat di Kelurahan Kebonmanis Cilacap - Siti Zahrotun Nisa; Dedy Riyadin Saputro (BANTENESE : JURNAL PENGABDIAN MASYARAKAT, 2021)
Garbage is a national problem and an important issue, especially in urban areas. In this case, the people of Kebonmanis took the initiative to reduce the impact caused by the accumulation of household waste by managing a waste bank. Household waste that was previously only disposed of in the landfill has now begun to be sorted and put to good use for activities in their respective environments, including in terms of increasing the income of the surrounding community. The activity begins with counseling, education, training and implementation. The purpose of this activity is to reduce the accumulation of household waste so that disasters do not occur and utilize waste with the creations and innovations of the surrounding community. In addition, to increase people's income by collecting and exchanging waste every week for basic food materials. The method used is observation, interviews, and documentation. The results show that the management of the waste bank provides many benefits to the surrounding community, the environment becomes comfortable, beautiful, green, and increases the economic income of the community. This activity received support from several parties such as the Cilacap government, the PKK driving team, LKM Makmur Kebonmanis, and PLN Peduli. The conclusion of this study is that household waste can bring benefits in terms of social, economic, and environmental positive impacts from the Waste Bank in Kebon Manis Village, Cilacap. The results show that the management of the waste bank provides many benefits to the surrounding community, the environment becomes comfortable, beautiful, green, and increases the economic income of the community. This activity received support from several parties such as the Cilacap government, the PKK driving team, LKM Makmur Kebonmanis, and PLN Peduli. The conclusion of this study is that household waste can bring benefits in terms of social, economic, and environmental positive impacts from the Waste Bank in Kebon Manis Village, Cilacap. The results show that the management of the waste bank provides many benefits to the surrounding community, the environment becomes comfortable, beautiful, green, and increases the economic income of the community. This activity received support from several parties such as the Cilacap government, the PKK driving team, LKM Makmur Kebonmanis, and PLN Peduli. The conclusion of this study is that household waste can bring benefits in terms of social, economic, and environmental positive impacts from the Waste Bank in Kebon Manis Village, Cilacap.